DNA Methylation and Brain‐Derived Neurotrophic Factor Expression Account for Symptoms and Widespread Hyperalgesia in Patients With Chronic Fatigue Syndrome and Comorbid Fibromyalgia. Issue 11 (7th October 2020) - Polli, Andrea; Ghosh, Manosij; Bakusic, Jelena; Ickmans, Kelly; Monteyne, Dora; Velkeniers, Brigitte; Bekaert, Bram; Godderis, Lode; Nijs, Jo
Abstract : Objective: The epigenetics of neurotrophic factors holds the potential to unravel the mechanisms underlying the pathophysiology of complex conditions such as chronic fatigue syndrome (CFS). This study was undertaken to explore the role of brain‐derived neurotrophic factor (BDNF) genetics, epigenetics, and protein expression in patients with both CFS and comorbid fibromyalgia (CFS/FM). Methods: A repeated‐measures study was conducted in 54 participants (28 patients with CFS/FM and 26 matched healthy controls). Participants underwent a comprehensive assessment, including questionnaires, sensory testing, and blood withdrawal. Serum BDNF (sBDNF) protein levels were measured using enzyme‐linked immunosorbent assay, while polymorphism and DNA methylation were measured in blood using pyrosequencing technology. To assess the temporal stability of the measures, participants underwent the same assessment twice within 4 days. Results: Repeated‐measures mixed linear models were used for between‐group analysis, with mean differences and 95% confidence intervals (95% CIs) shown. Compared to controls, serum BNDF was higher in patients with CFS/FM (F = 15.703; mean difference 3.31 ng/ml [95% CI 1.65, 4.96]; P = 0.001), whereas BDNF DNA methylation in exon 9 was lower (F = 7.543; mean difference −2.16% [95% CI −3.93, −0.83]; P = 0.007). BDNF DNA methylation was mediated by the Val66Met (rs6265) polymorphism. Lower methylation in the same region predicted higher sBDNF levels (F = 7.137, β = −0.408 [95% CI −0.711, −0.105]; P = 0.009), which in turn predicted participants' symptoms (F = 14.410, β = 3.747 [95% CI 1.79, 5.71]; P = 0.001) and widespread hyperalgesia (F = 4.147, β = 0.04 [95% CI 0.01, 0.08]; P = 0.044). Conclusion: Our findings indicate that sBDNF levels are elevated in patients with CFS/FM and that BDNF methylation in exon 9 accounts for the regulation of protein expression. Altered BDNF levels might represent a key mechanism explaining CFS/FM pathophysiology.